Implementasi Kebijakan Pengendalian Massa di Wilayah Hukum Polres Morowali Utara - Haris, Haris; Mustainah, Mustainah; Natsir, Nawawi (Journal of Education Religion Humanities and Multidiciplinary, 2025)
The results of this study indicate that the implementation of the Crowd Control Policy in the jurisdiction of the North Morowali Police has not been running optimally, this is due to the failure to achieve the Communication Aspect between implementers has not run well. Coordination between leaders and members in the field still often experiences obstacles, especially in conveying information quickly and accurately when urgent situations occur. and communication in handling crowd control demonstrations has not run well because the masses who hold demonstrations are always in unexpected circumstances without prior notification. The Resource Aspect, both personnel and infrastructure owned by the North Morowali Police Samapta Unit is still relatively limited. The number of personnel on duty is not proportional to the area and intensity of community activities. The Disposition Aspect that the commitment and integrity of implementers in the field is quite good, where Samapta members try to carry out crowd control tasks by upholding the principles of professionalism and proportionality. The Bureaucratic Structure Aspect, in the implementation of the crowd control policy at the North Morowali Police has been clearly structured and in accordance with Standard Operating Procedures (SOP) and has a clear division of tasks, starting from planning, implementation, to evaluation